2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2019
DOI: 10.1109/cvprw.2019.00336
|View full text |Cite
|
Sign up to set email alerts
|

Solo or Ensemble? Choosing a CNN Architecture for Melanoma Classification

Abstract: Convolutional neural networks (CNNs) deliver exceptional results for computer vision, including medical image analysis. With the growing number of available architectures, picking one over another is far from obvious. Existing art suggests that, when performing transfer learning, the performance of CNN architectures on ImageNet correlates strongly with their performance on target tasks. We evaluate that claim for melanoma classification, over 9 CNNs architectures, in 5 sets of splits created on the ISIC Challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Several methods have been proposed to enhance robustness against corruptions; these include mixed data augmentation [37], adversarial noise training [38], and assembling CNN techniques with KD [39]. However, in the skin lesion analysis domain, wherein random nuisances are observed, the correlation between the network and metrics is difficult to analyze from the ImageNet perspective [26]. Furthermore, methods that improve corruption robustness have not yet been extensively tested for a skin lesion analysis.…”
Section: Efficiency and Robustness Of Dnnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been proposed to enhance robustness against corruptions; these include mixed data augmentation [37], adversarial noise training [38], and assembling CNN techniques with KD [39]. However, in the skin lesion analysis domain, wherein random nuisances are observed, the correlation between the network and metrics is difficult to analyze from the ImageNet perspective [26]. Furthermore, methods that improve corruption robustness have not yet been extensively tested for a skin lesion analysis.…”
Section: Efficiency and Robustness Of Dnnsmentioning
confidence: 99%
“…Perez. et al conducted extensive experiments for melanoma classification [26] with 135 models, and they showed that the ensembles of neural networks perform significantly better than a single model, even when the models used for the ensemble are randomly selected. However, the ensemble of the neural networks leads to a heavy and larger model, which is infeasible for mobile on-device inference and mobile diagnostic services.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the spectral heterogeneity in HR-RS images and the occlusions on roads, mistakes of road extraction are inevitable even for the state-of-the-art models. Creating ensembles of multi-models is proved to be an effective way of improving accuracies in CNN methods, because models trained with different architectures or hyper-parameters may have complementary information [40][41][42].…”
Section: Ensemble Strategymentioning
confidence: 99%
“…In addition, his work only uses the U-Net [12] as G which can be improved by other state-of-the-art segmentation models such as BiSeNet [22]. And to further improve the overall performance in CNN methods, creating ensembles of multi-models may be an effective way [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…AI classifiers for the image classification field have been dramatically improved and made more popular by the introduction of CNN. Many strategies, such as creating ensembles of multiple models (62, 63) or using additional information other than image labels, to improve the accuracy of the classifier outside of increasing the number of images for training have been reported (64). Some studies have reported that CNN algorithms have already surpassed the classification efficacy of dermatologists and, in the near future, AI classifiers may gain sufficient sensitivity and specificity to bear the screening burden for detecting malignant skin tumors.…”
Section: Future Perspectivementioning
confidence: 99%